The complete book of option spreads and combinations : - Nations, Scott (John Wiley & Sons, Inc., 2014)
This book tells us about: Generate monthly income by selling covered strangles Use call spreads to recover from a losing stock position Protect an existing stock position using put diagonals Discover the best strategies for directional market plays